2011
DOI: 10.1021/jp110927j
|View full text |Cite
|
Sign up to set email alerts
|

Two-Dimensional Time-Dependent Numerical Modeling of Edge Effects in Dye Solar Cells

Abstract: A two-dimensional transient model of dye solar cells (DSC) describing the electrochemical reactions in the cell has been prepared. The model includes the relevant components of DSCs: the photoelectrode, the electrolyte, and the counter electrode. The solved variables are potential and the concentrations of the dierent ion species, which can be used to determine e.g. the current-voltage characteristics of the cell. The largest benet of this model is its 2D features which enable the study of lateral inhomogeneit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 46 publications
0
21
0
Order By: Relevance
“…In practice this means that it is not practically possible to get the electrodes aligned that well and there will be drifts. The drifts are, however, relatively slow; it takes almost ten minutes for the ions to diffuse over the distance of 0.5 mm between the adjacent segments 9 and here the distance between the segments was even larger (2 mm). This means that short measurements (in the range of a couple of minutes) such as IV and IPCE are not significantly affected whereas hours long electrochemical impedance spectroscopy (EIS) measurements very likely are.…”
Section: Cell Preparationmentioning
confidence: 85%
“…In practice this means that it is not practically possible to get the electrodes aligned that well and there will be drifts. The drifts are, however, relatively slow; it takes almost ten minutes for the ions to diffuse over the distance of 0.5 mm between the adjacent segments 9 and here the distance between the segments was even larger (2 mm). This means that short measurements (in the range of a couple of minutes) such as IV and IPCE are not significantly affected whereas hours long electrochemical impedance spectroscopy (EIS) measurements very likely are.…”
Section: Cell Preparationmentioning
confidence: 85%
“…The high value of J sc for Ag sensitizers may be due to its high light harvesting efficiency (LHE) because the value of J sc is directly influenced by the light harvesting efficiency and electron injection efficiency. Moreover, the light harvesting efficiency is directly influenced by the optical absorption [41]. The high absorption and, thus, the high LHE of Ag might be the reason for enhancement of J sc in MCSC constructed from Ag CLs.…”
Section: Photo-electrochemical Responsementioning
confidence: 99%
“…Miettunen et al developed a numerical 2D transient model of n-DSCs and found that the concentration of I 3 − at the photoelectrode side increases from ∼30 mol m −3 to ∼45 mol m −3 in a working cell. 45 Barnes et al presented a complete numerical simulation of n-DSCs to assess the importance of different loss pathways under various operational conditions. At SC under 1 sun illumination, the concentration of I 3 − in the 12.5 μm TiO 2 film increases from the initial 0.05 to ∼0.12 M. 46 The variation of local iodide concentration in our NiO p-DSCs should be smaller because the net reaction at TiO 2 photoanode or NiO photocathode is the conversion between I 3 − and I − , and the photocurrent of the p-DSC is one order of magnitude lower.…”
Section: Recombination At Nio/dye/electrolytementioning
confidence: 99%